European experience in human resource management in higher education institutions (Journal of Economic Research & Business Administration, 2019)
The article examines the experience of the academic staff management as the main force for the implementation of the educational process in higher educational institutions of European countries. Comparative analysis of the key aspects of human resources management in universities of Europe, personnel selection, recruitment, employment and professional development has been made. The purpose of thestudy is to familiarize with the experience of the academic staff formation ways, which are involved inthe educational process, the requirements for the academic staff, their pedagogical load, weekly workinghours, selecting process of them and organization of the training programs, working conditions inEuropean universities. During the research, the authors used common scientific methods and techniqueslike analysis, synthesis, comparison, and generalization of data with corresponding conclusions. Accordingto the results of the study the practice of human resources management experience has differencebetween the countries of Europe due to the different level of socio-economic development of the country,financial capabilities of each University, and the mechanisms for the implementation of strategicplans. For example, Austrian universities select academic staff for vacancies in lower-level positions onan open basis, for associate-level positions on the basis of career growth, and University professors onthe basis of a combination of these two factors. In some countries of the European Union, in particularNorway, Switzerland, Greece, Hungary, Slovenia, academic staff of higher education institutions arerecognized as public servants by law, and this makes it possible to optimally address the issues of theirlong-term employment, favorable working conditions and wages. In Czech Republic, Poland, Slovakiaand Hungary, the title of professor is appointed by the head of the country, while the Italian Ministry ofEducation, University and Research bases on a competitive evaluation committee decision. The practicalsignificance of the study is that in the context of the Bologna process the successful experience andthe best models of European country universities on the academic staff management can be applied inthe higher education institutions of Kazakhstan taking into account the national characteristics of thecountry. It has positive effect on increasing competitiveness of the economy by training a high qualified,smart, and talent professionals.